FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MELAKUKAN AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Sonya Mawariani Putri; Desmiyawati '; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The data used in this research are company listed in Bursa Efek Indonesia (BEI) in the year 2009-2012. The factors used on this research are KAP size, size of client companies, growth companies, FinancialDistress, and audit opinion. Sampling was purposive sampling method that produced 20 companies sample. Hypotesis testing on this research was done by the logistic regression analysis.The analysis showed that the type of KAP, size of client companies, and audit opinion significantly influence the possibility of change of KAP. Companies with KAP big 4 have a lower chance to experience changing of KAP than the company with the KAP non big 4. growth companies (as measured by total assets) and financial problems did not significantly influence the factors that influence the change of auditor in Indonesia.Keywords: Auditor Switching, KAP size, size of client companies, growth companies, Financial Distress, and audit opinion.